Rural life: Issues on Legal Regulation - A. A. Afanasyev (Сибирское юридическое обозрение, 2014)
On the basis of scientific legal literature, social studies, law enforcement practice here are highlighted the problems of legal regulation of rural life. Emphasizes is made on the importance of the regulatory function of law. The author proposes some measures for its strengthening in achieving the objectives of the state policy on sustainable integrated economic and social development of rural areas.